1992
DOI: 10.1152/ajpregu.1992.263.3.r624
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of respiration and swallowing: effect of bolus volume in normal adults

Abstract: The coordination of swallowing and respiration, as measured by nasal airflow, and the effect of changes in the volume of the swallow bolus (0-20 ml) were investigated in 12 normal subjects. Both nonbolus and bolus swallows were usually preceded and followed by expiratory airflow. Swallows followed by inspiratory airflow accounted for 20% of nonbolus swallows but decreased further in frequency in the presence of a bolus. Swallowing was associated with an apneic period lasting 1.90 +/- 0.26 s for nonbolus swallo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
80
2
4

Year Published

1994
1994
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(99 citation statements)
references
References 0 publications
12
80
2
4
Order By: Relevance
“…The findings of this study demonstrated that normal elderly female mean SAD on a 25 ml bolus was 1.32 s whereas normal young female mean SAD on a 10 ml bolus was .77 s. Thus, if a researcher or clinician obtains a SAD value from a participant/patient without respect to age or bolus volume an incorrect assumption may be made as to the increased or decreased nature of its duration. The lack of a significant bolus volume effect on SAD reported by Martin et al [2] and Preiksaitis et Swallowing Apnea Duration 13 al. [13] may be a consequence of employing a small sample size and limited bolus volumes.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…The findings of this study demonstrated that normal elderly female mean SAD on a 25 ml bolus was 1.32 s whereas normal young female mean SAD on a 10 ml bolus was .77 s. Thus, if a researcher or clinician obtains a SAD value from a participant/patient without respect to age or bolus volume an incorrect assumption may be made as to the increased or decreased nature of its duration. The lack of a significant bolus volume effect on SAD reported by Martin et al [2] and Preiksaitis et Swallowing Apnea Duration 13 al. [13] may be a consequence of employing a small sample size and limited bolus volumes.…”
Section: Discussionmentioning
confidence: 89%
“…Klahn and Perlman [21] reported similar percentages where apneic onset occurred during expiration 93% of the time and was succeeded by expiration 100% of the time across 5-ml water and applesauce boluses. In contrast, however, Preiksaitis, et al [13] reported a marked smaller percentage of 71.4% of swallows exhibited an exhale-swallow-exhale pattern. Moreover, Preiksaitis and Mills [14] reported the pattern of exhale-swallow-exhale was present in 77% of 100 swallows, yet this pattern decreased Klahn and Perlman [21] acknowledged the disparity in the reported data relating to SA and called for a larger body of normative data from a larger number of participants to confirm their findings.…”
mentioning
confidence: 89%
See 3 more Smart Citations